(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
For software products, the specifications, the requirements even the variables, the code or the software modules are subject to be labelled with key-terms, or described using attributes or specific values. The purpose of these notations is linked to the semantic of the object labelled, and is used as an indexing form for that specific category. A separation of concerns meta model is proposed here to provide the support of using a unitary type of notation in labelling various kind of resources used in the process of developing software, from requirements and specifications all the way to variables, code or software modules. The use of a standard, unitary notation can have multiple benefits, covering areas like code reusability, reverse engineering, assigning technologies for development, aspect-oriented software development (AOSD), requirements engineering (engineering web applications, grouping requirements by categories, such as: technology, importance, actor, volatility, functionality).